2019
DOI: 10.21203/rs.2.16856/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inpatient admissions and costs for adolescents and young adults with congenital heart defects in New York, 2009-2013

Abstract: Background Most individuals born with congenital heart defects (CHDs) survive to adulthood, but healthcare utilization patterns for adolescents and adults with CHDs have not been well described. We sought to characterize the healthcare utilization patterns and associated costs for adolescents and young adults with CHDs.Methods We examined 2009-2013 New York State inpatient admissions of individuals ages 11-30 years with ≥1 CHD diagnosis codes recorded during any admission. We conducted multivariate linear regr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…114 In New York State, between 2009 and 2013, total costs of inpatient admission for individuals 11 to 30 years of age with CCDs rose from $27.2 million in 2009 to $52.2 million in 2013, increasing faster for those with nonsevere versus severe CCD. 115 A Pediatric Heart Network study found an overall cost reduction for TOF repair of 27% after a clinical practice guideline including early extubation was introduced. Similar cost reduction was not found for patients with aortic coarctation repair.…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…114 In New York State, between 2009 and 2013, total costs of inpatient admission for individuals 11 to 30 years of age with CCDs rose from $27.2 million in 2009 to $52.2 million in 2013, increasing faster for those with nonsevere versus severe CCD. 115 A Pediatric Heart Network study found an overall cost reduction for TOF repair of 27% after a clinical practice guideline including early extubation was introduced. Similar cost reduction was not found for patients with aortic coarctation repair.…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%
“…In New York State, between 2009 and 2013, total costs of inpatient admission for individuals 11 to 30 years of age with CCDs rose from $27.2 million in 2009 to $52.2 million in 2013, increasing faster for those with nonsevere versus severe CCD. 115…”
Section: Congenital Cardiovascular Defects and Kawasaki Diseasementioning
confidence: 99%